G315 Providing healthy food choices in hospital: Are we failing our patients?. (27th April 2016) - Tolan, S; Ayling, H; Knight, K; Singh, C
Abstract : Aims: Obesity in children and young people in the United Kingdom is increasing in prevalence. The responsibility of paediatricians extends to the promotion of healthy eating; balanced nutrition being of increased importance for the unwell child. The presented study evaluates the food options readily available to children in a large district general hospital, against a healthy eating model as suggested by NICE Quality Standard 94. Method: Food options presented in hospital vending machines, served on the children's ward and in the canteen were analysed for the proportion of healthy options and availability of nutritional information at the point of selection. Results: Vending machines; 22% of the items displayed clear nutritional information. Available products comprised of chocolate (28%), biscuits (21%), crisps (19%) and artificial drinks (11%). Natural drinks accounted for 4% of the contents. Ward; A daily menu is used throughout the hospital, serving only adult portions on the paediatric wards. The menu delineates healthy options with a heart symbol (37%), meals with high energy (31%), softer diet (46%), vegetarian options (56%) and gluten free options (54%). Full nutritional breakdown is available only on request. Canteen; Items produced on site have a ticket detailing energy, total fat, saturates, sugar and salt content per adult portion. 86 menu items were analysed. 68% of main dishes, 22% of sides, 80% of desserts and 57% of breakfast items were classified as 'unhealthy', (Department of Health guidance for nutritional labelling). Conclusion: The range of food available in hospital is skewed to an unhealthy predominance. Nutritional information is displayed inconsistently and with ambiguity, challenging parental decision making for healthier choices. A unified, comprehensible system is required throughout the catering services. Implementation: A collection of posters and leaflets designed to demonstrate the importance of healthy eating and exercise has been created to display across the hospital and distribute to parents and children to educate patient choices. In collaboration, work continues towards implementing the nationally recommended traffic light approach to food labelling across hospital catering services and adjusting the selection at vending machines to offer healthier options.